UTILITY OF CALGARY–CAMBRIDGE MODEL TO ENHANCE COMMUNICATION SKILL IN HISTORY TAKING FOR PHASE II MBBS LEARNERS - Dr. Ankana Chakraborty; Dr. Rajarshi Gupta; Dr. Sujoy Sankar Bhattacharjee; Dr. Bonapart Chowdhury (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundAETCOM module was incorporated in CBME curriculum few years ago. There are several models of communication during clinical consultations, among which Calgary–Cambridge model was used in this cross-sectional study to evaluate its utility in enhancing communication skill in medical learners.MethodsA total of 100 consenting 2nd Professional MBBS learners were randomly selected for this study and all of them had undergone training sessions in communication and counseling skills using Calgary–Cambridge model as a guide. Subsequently, participants interacted with all categories of adult indoor patients. At baseline and after completion of training, their communication skills were assessed by using Kalamazoo Communication Assessment tool and Standardized Patient Satisfaction Questionnaire. Their attitude and knowledge were assessed using Communication Skills Attitude Scale and pre-test & post-test MCQs respectively.ResultsIn our study, comparative analysis of the pre and post training OSCE (Kalamazoo Communication Assessment tool) scores and SPSQ scores using Wilcoxon signed ranks test revealed that the post training scores of all components including total scores were significantly higher than pre training scores (p < 0.00001, effect size 0.87 for both OSCE and SPSQ). There was significant gain in knowledge about communication skills as revealed by the significantly higher post training MCQ test scores (p value < 0.0001, effect size 3.72). All the participants had a positive attitude toward learning communication skills. ConclusionAs depicted by Communication Skill Attitude Scale, participants’ positive attitude toward learning communication skill indicated that there is a necessity of communication skill training. Hence, it can be concluded that Calgary–Cambridge model is an effective way to enhance communication skill in history taking for Phase II MBBS learners.